Brazilian version of the Self-Estimated Functional Inability because of Pain questionnaire for musculoskeletal injuries relating to dance and sport: translation and cross-cultural adaptation - Reis-Júnior, Jodimar Ribeiro dos (2020)
BACKGROUND: Self-Estimated Functional Inability because of Pain (SEFIP) is a questionnaire specifically designed to measure musculoskeletal pain or discomfort. OBJECTIVE: To perform translation and cross-cultural adaptation of the SEFIP for dancers (SEFIP-dance), for use in Brazilian Portuguese. In addition, as a secondary objective, we adapted the translated version of SEFIP-dance for use among athletes or exercise practitioners (SEFIP-sport). DESIGN AND SETTING: Questionnaire translation and cross-cultural adaptation study conducted at a public university. METHODS: The Brazilian version of the SEFIP-dance questionnaire was developed following the processes of translation (involving two translators with Brazilian Portuguese as their mother tongue and fluency in English), backtranslation (involving two translators with English as their mother tongue and fluency in Brazilian Portuguese), committee review and pre-testing. SEFIP-sport was developed following the processes of content and face validation. RESULTS: SEFIP-dance was applied to 30 dancers, of mean age 22.38 years (standard deviation [SD] = 3.41), among whom 14 were men (46.66%). The participants understood 100% of the SEFIP-dance items and alternatives. SEFIP-sport was applied to 30 athletes or physical exercise practitioners, of mean age 25.09 years (SD = 8.93), among whom 25 were men (86.33%). The participants understood 100% of the SEFIP-sport items and alternatives. CONCLUSION: The Brazilian Portuguese versions of SEFIP-dance, translated and cross-culturally adapted for dancers, and SEFIP-sport, adapted for athletes or physical exercise practitioners, were shown to have adequate levels of understanding.